MANAGEMENT INSTITUTE LIBRARIES JOB SATISFACTION BIHAR - Manoj Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
This situation puts the librarian far from being satisfied. Because of the state of the economy, particularly the social amenities are adequate. Demotivating factors include low earnings, a lack of social standing, and inadequate social security. When it comes to work, there is no such thing as job happiness if there is a lack of motivation. The level of job satisfaction that a librarian, who occupies an important position in the information society, experiences will have an effect on the quality of the service that he provides. In this light, the inquiry into the ways in which the material and moral components contribute to the level of job satisfaction experienced by librarians takes on a greater level of significance. It has been said that job satisfaction is a pleasant emotional state that results from the appraisal of one's employment, an affective reaction to one's job, and an attitude towards one's job. Weiss contends that job satisfaction is an attitude, but he emphasises that researchers need to make a distinct distinction between the objects of cognitive evaluation, which are affect (feeling), beliefs, and behaviours. This definition implies that we build attitudes regarding our occupations by taking into consideration our feelings, our beliefs, and the activities that we engage in.